200 Effects of grain processing and undegradable fiber on rumen pH and fermentation of cattle fed high grain diets. (30th November 2020) - Ran, Tao; Saleem, A M; Beauchemin, Karen; Penner, G; Yang, Wenzhu
Abstract: The objective of this study was to investigate the effects of processing index (PI, weight after processing/weight before processing × 100) of barley grain and dietary undegradable fiber (uNDF, 240 h of incubation in rumen) concentration on DM intake (DMI), ruminal pH and fermentation characteristics of finishing beef cattle. Six ruminally cannulated beef heifers (BW, 715 ± 29 kg) were used in a 6 × 6 Latin square design with 3 PI (65, 75 and 85%; fine, medium, coarse, respectively) × 2 uNDF concentrations (low and high; 4.6 vs. 5.6% of DM) factorial arrangement. Heifers were fed ad libitum a diet consisting of 10% barley silage (low uNDF), or 5% silage and 5% straw (high uNDF), 87% dry-rolled barley, and 3% vitamin and mineral supplements. An interaction of PI × uNDF was observed (P < 0.01) for DMI, but not for mean or duration of rumen pH < 5.8 or < 5.6 over a 24-h period. The DMI (kg/d) was greater (P < 0.05) for high (12.7) versus low (12.1) uNDF diets with 85% PI, with no difference in DMI (average, 12.1) between low and high uNDF diets with 65 or 75% PI. The duration of pH < 5.8 (14.6 versus 13.3 h) and pH < 5.6 (10.8 versus 8.6 h) reduced (P < 0.05) for high versus low uNDF diets. The PI did not affect total volatile fatty acid (tVFA) concentration or molar proportions of individual VFA, but the tVFA was less (172 and 162 mM; P < 0.01) and acetate proportion was greater (46.0 and 48.2%; P < 0.01) with high versus low uNDF. These results indicate that increasing dietary uNDF concentration is an effective strategy to improve ruminal pH status in finishing cattle, regardless of extent of grain processing, whereas minimizing the extent of grain processing did not reduce the risk of rumen acidosis.